SHOX haploinsufficiency presenting with isolated short long bones in the second and third trimester - Ramachandrappa, S; Kulkarni, A; Gandhi, H; Ellis, C; Hutt, R; Roberts, L; Hamid, R; Papageorghiou, A; Mansour, S (Springer Nature, 2018)
Haploinsufficiency of the transcription factor short stature homeobox (SHOX) manifests as a spectrum of clinical phenotypes, ranging from disproportionate short stature and Madelung deformity to isolated short stature. Here, we describe five infants with molecularly confirmed diagnoses of SHOX haploinsufficiency who presented in utero with short long bones during routine antenatal scanning from as early as 19 weeks gestation. Other foetal growth parameters were normal. The molecular basis of SHOX haploinsufficiency was distinct in each case. In four cases, SHOX haploinsufficiency was inherited from a previously undiagnosed parent. In our de novo case, SHOX haploinsufficiency reflected the formation of a derivative sex chromosome during paternal meiosis. Final adult height in the SHOX-deficient parents ranged from -1.9 to -1.2 SDS. All affected parents had disproportionately short limbs and two affected mothers had bilateral Madelung deformity. To our knowledge, SHOX haploinsufficiency has not previously been reported to present in utero. Our experience illustrates that SHOX deficiency should form part of the differential diagnosis of foetal short long bones and suggests a low threshold for genetic testing. This should be particularly targeted at, but not limited to, families with a history of features suggestive of SHOX deficiency. Data on the postnatal growth of our index cases is presented which demonstrates that antenatal presentation of SHOX haploinsufficiency is not indicative of severe postnatal growth restriction. Early identification of SHOX deficiency will enable accurate genetic counselling reflecting a good postnatal outcome and facilitate optimal initiation of growth hormone therapy.